PENGARUH RELATIONSHIP MARKETING DAN EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN PADA KLINIK KECANTIKAN BENING’S CLINIC SURABAYA - Andika, Shelia Tiara; Maduwinarti, Ayun; Nasution, Ute Chairuz M. (Research Journal of Social Science and Economics, 2025)
In the current era of globalization, it is very difficult to keep consumers loyal to the company. Companies must improve and always update the system in their marketing strategy in order to retain their customers in the long term. The appropriate strategy, namely relationship marketing, is a marketing strategy for how companies establish good relations with consumers so that they use their products / services again. Basically, customer satisfaction is highly expected by the company, because the experience felt by consumers can reflect how much consumers like or dislike the company. Therefore, companies must be able to maintain and provide memorable experiences to their customers so that they can foster customer satisfaction. To provide a memorable experience, the strategy chosen by the company is to implement an experiential marketing strategy. The purpose of this study was to determine the influence of relationship marketing and experiential marketing on customer satisfaction significantly. As for supporting this research is done by using quantitative methods. The research instruments were in the form of questionnaires and assistance through the SPSS 20 program. Before testing the hypothesis, the data were tested for validity and reliability. To test the hypothesis using multiple regression analysis, t test, F test and R² test. To get good regression results, the classical assumption test was previously carried out. The population studied was all consumers of Bening's Clinic Surabaya who did the treatment. The sample used is 100 people. The results of this study indicate that there is a significant influence between relationship marketing and experiential marketing on customer satisfaction at Bening's Beauty Clinic Surabaya. Keywords: Relationship Marketing, Experiential Marketing, Consumer Satisfaction